Regulation of cAMP Responsive Element Binding Protein 3-Like 1 (Creb3l1) Expression by Orphan Nuclear Receptor Nr4a1 - Greenwood, Michael P.; Greenwood, Mingkwan; Gillard, Benjamin T.; Chitra Devi, R.; Murphy, David (Frontiers in Molecular Neuroscience, 2017)
cAMP inducible transcription factor Creb3l1 is strongly activated in the hypothalamus in response hyperosmotic cues such as dehydration. We have recently shown that Creb3l1 expression is upregulated by cAMP pathways in vitro, however the exact mechanisms are not known. Here we show that increasing Creb3l1 transcription by raising cAMP levels in mouse pituitary AtT20 cells automatically initiates cleavage of Creb3l1, leading to a greater abundance of the transcriptionally active N-terminal portion. Inhibiting protein synthesis indicated that de novo protein synthesis of an intermediary transcription factor was required for Creb3l1 induction. Strategic mining of our microarray data from dehydrated rodent hypothalamus revealed four candidates, reduced to two by analysis of acute hyperosmotic-induced transcriptional activation profiles in the hypothalamus, and one, orphan nuclear receptor Nr4a1, by direct shRNA mediated silencing in AtT20 cells. We show that activation of Creb3l1 transcription by Nr4a1 involves interaction with a single NBRE site in the promoter region. The ability to activate Creb3l1 transcription by this pathway in vitro is dictated by the level of methylation of a CpG island within the proximal promoter/5’UTR of this gene. We thus identify a novel cAMP-Nr4a1-Creb3l1 transcriptional pathway in AtT20 cells and also, our evidence would suggest, in the hypothalamus.